STUDI RISIKO EKONOMI PENJUALAN WORTEL (Daucus carota L.) VARIETAS CHANTENAY DAN IMPERATOR DI TINGKAT PENGECER PASAR SEGIRI KOTA SAMARINDA (Economic Risk Study of (Daucus carota L.) Carrot Sale of Chantenay and Imperator Varieties in Retailer Level of Segiri Market Samarinda City) - ADE MARTHA AISYAH; SITI BALKIS; RITA MARIATI (Universitas Mulawarman (University of Mulawarman), 2019)
The risk will be faced by retailers in marketing of local carrots with chantenay and imperator varieties. The purposes of this study were to know the economic risk (revenue and income) that is influenced by the risk of total inventory and selling price that will be faced by carrot retailers in Segiri Market, Samarinda City. This research was conducted for 5 months from April to August 2018. Sampling method in this study was purposive sampling. The data collected in this study were primary and secondary data. The data analytical used the E-V (Hope- Variance) risk analysis. The results showed that the risk of inventory is as many as 21.7% for the chantenay variety and as many as 17.4% for the imperator variety. The risk of selling price was Rp13,576.00 for the chantenay variety and Rp11,771.00 for the imperator variety. The retailers in Segiri Market, Samarinda City have economic risk in terms of revenue and income in the amount of 49.8% and 64.2% for chantenay carrots variety while for imperator variety of 40.4% and 55.3%.